2014
DOI: 10.1111/evo.12527
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the strength of inbreeding depression across environments: Effects of stress and density dependence

Abstract: In what types of environments should we expect to find strong inbreeding depression? Previous studies indicate that inbreeding depression, δ, is positively correlated with the stressfulness of the environment in which it is measured. However, it remains unclear why stress, per se, should increase δ. To our knowledge, only "competitive stress" has a logical connection to δ. Through competition for resources, better quality (outbred) individuals make the environment worse for lower quality (inbred) individuals, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
55
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 26 publications
4
55
6
Order By: Relevance
“…Thus, our results do not support the findings of Yun and Agrawal (2014), who found that ID was strongest when competition was intense. We found that, although competition resulted in a slightly higher ID than the other stressors, its effect was very similar to that of heat, while the other two stressors (ethanol and bacteria) induced very similar levels of ID (see Figure 2a), pairings that suggest no particular pattern.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Thus, our results do not support the findings of Yun and Agrawal (2014), who found that ID was strongest when competition was intense. We found that, although competition resulted in a slightly higher ID than the other stressors, its effect was very similar to that of heat, while the other two stressors (ethanol and bacteria) induced very similar levels of ID (see Figure 2a), pairings that suggest no particular pattern.…”
Section: Discussioncontrasting
confidence: 99%
“…Predicting the outcome of inbreeding-stress interactions centers on the concept that stress alters the strength of selection against deleterious alleles that cause ID (Agrawal and Whitlock, 2010;Yun and Agrawal, 2014). The finding that the intensity of stress scales positively with ID in a variety of taxa (Fox and Reed, 2011;Enders and Nunney, 2012;Schou et al, 2015) supports the general prediction that selection is greater in stressful environments.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…In most cases, the negative effects of inbreeding (or the positive effects of outbreeding) have been found more often among females than males. The differences in the effects of heterozygosity or inbreeding between males and females may be explained by sex-specific gene expression (Yun and Agrawal 2014), maternal investments (Charpentier et al 2006), food acquisition (Charpentier et al 2006), growth strategies (Coulson et al 1998), sexual selection pressure and life history (Ebel and Phillips 2016).…”
Section: Introductionmentioning
confidence: 99%